2012
DOI: 10.1097/hjh.0b013e32834f6f3f
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive MRI analysis of early cardiac and vascular remodeling in middle-aged patients with abdominal obesity

Abstract: Concentric remodeling is frequently documented by MRI in the middle-aged men with abdominal obesity and in association with a decrease in TAC no longer counter-balanced by a decrease in TPVR, suggesting a remodeling from proximal to peripheral vasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…Forth, TAC is a crude indicator of global arterial stiffness based on a modified two-factor Windkessel model combining resistance and capacitance. As such, TAC is limited in describing all components of arterial mechanics [40]. Finally, there were limitations of our 2D phase contrast sequence used to calculate PWV and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Forth, TAC is a crude indicator of global arterial stiffness based on a modified two-factor Windkessel model combining resistance and capacitance. As such, TAC is limited in describing all components of arterial mechanics [40]. Finally, there were limitations of our 2D phase contrast sequence used to calculate PWV and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Each plane was recorded as previously detailed [8, 9, 16], and LV end-diastolic volume (EDV), end-systolic volume and ejection fraction (EF) were obtained by an expert cardiologist, using dedicated software (MASS research v2013-exp™, Medis, Leiden University Medical Center, The Netherlands). Main acquisition parameters were as follows: 8 mm slice-thickness, 3.5–3.9 ms repetition time, 14 to 16 K-space lines per segment, 1.5 ASSET factor, 30 phases per cardiac cycle with view sharing, field-of-view (FOV) ranging from 32 to 38 cm with a phase FOV of 0.9, and a 224x224 matrix interpolated to 256x256.…”
Section: Methodsmentioning
confidence: 99%
“…The combined analysis of brachial blood pressure (BP) and of the SV producing the BP wave has been recently shown to significantly improve the CMR characterization of LV remodeling in hypertensive patients [8, 9]. This improvement is notably due to the precise information obtained on LV loading conditions with the non-invasive determination of various parameters such as total peripheral vascular resistance, total arterial compliance index and effective arterial elastance [813].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we previously described thanks to an MRI substudy that there was no difference in aortic PWV between controls and patients with AO. 39 We may hypothesize that arterial changes may not have occurred yet in the subjects we have investigated, who were young and normotensives. Circulating collagen peptides are not specific to cardiac tissue, but previous histological studies observed a significant correlation between collagen peptides serum concentrations and cardiac fibrosis.…”
mentioning
confidence: 95%